IgG4-related hypophysitis diagnosed by retroperitoneal mass biopsy in a patient presenting with abducens nerve palsy: A case report (CARE-compliant article). Issue 40 (2nd October 2020) - Imai, Takeshi; Shibata, Souichirou; Shinohara, Kensuke; Sakurai, Kenzo; Horiuchi, Masahiro; Sakai, Kensuke; Asai, Shiko; Hasegawa, Yasuhiro
Abstract: Rationale: Immunoglobulin G4 (IgG4)-related hypophysitis is a rare disorder which often requires invasive pituitary gland biopsy to confirm its diagnosis. We present a case whereby peripheral organ lesion biopsy and imaging findings were sufficient for the diagnosis. Patient concerns: A 77-year-old man with diplopia was referred to our department by an opthomologist who had diagnosed the patient with right abducens nerve palsy. Diagnoses: Head magnetic resonance imaging revealed enlargement of the pituitary gland and pituitary stalk, while hormonal analysis revealed panhypopituitarism, thereby indicating a diagnosis of hypophysitis. Abdominal computed tomography imaging revealed a solid mass that encompassed the left kidney ureter. Although the patient did not have an increase in serum IgG4, a biopsy of the periureteral mass revealed infiltrating plasma cells that were positive when stained for IgG4. Interventions: The patient was given corticosteroid pulse therapy (methylprednisolone: 1 g × 3 days), followed by oral corticosteroids (prednisolone, 0.5 mg/kg/d). Outcomes: The right abducens nerve palsy improved and the pituitary lesion shrank after the initiation of corticosteroid treatment. Conclusion: Based on the diagnosis of IgG4-related disease in the retroperitoneal organ and response to corticosteroid treatment, this patient was diagnosed with IgG4-related hypophysitis. This hypophysitis caused enlargement of the pituitary gland with resulting nerve compression, causing abducens nerve palsy. When IgG4-related hypophysitis is suspected, a thorough examination of other organ lesions and biopsy should be considered.